Program “Mindful Parenting” untuk Meningkatkan Kesejahteraan Subjektif Ibu yang Memiliki Anak Retardasi Mental - Martaria Rizky Rinaldi; Sofia Retnowati (Faculty of Psychology, Universitas Gadjah Mada, 2016)
Parenting child with intellectual disability is associated with physical and psychological problems that influence mother’s subjective well-being. The evidence is show that mindfulness based intervention can increase of life satisfaction, elicit positive affect, dan minimize negative affect, so that it can increase subjective well-being. The aim of this study is to examine the effectiveness of “Mindful parenting” program in increasing subjective well-being mother who has child with intellectual disability. This study uses a one-group pretest-posttesttt design using a double pretest. “Mindful Parenting” program was administered to ten mothers of children with intellectual disability. Participant attend 8 sessions of “Mindful parenting” program in four meeting. Analysis using Friedman test showed significance result (Fr(2) = 11.13, p< 0.05). It conclude that there was significant effect of “Mindful parenting” program on promotes subjective well-being of mothers of children with intellectual disability.